Connected Type Integrated Science Learning Model of Student Learning Outcomes: Meta-Analysis - Dhea Febriya; Asrizal; Usmeldi (Jurnal Penelitian Pendidikan IPA, 2023)
Research Meta-analysis it aims to see magnitude of influence Integrated Science Learning Model Connected to the learning outcomes of participants educate. The research method used is meta-analysis, with a research sample amount 15 scientific articles that have been published through Google Scholar accredited _ And indexed Sinta, discussing national scale Integrated Science Learning Model Connected to learning outcomes, in 2012 - 2022. The research results obtained: Effect Â Integrated Science Learning with the Connected Model at the education level obtained an effect size value at the junior high school level that was higher than at the elementary school level and high school, Â Influence The Integrated Science Learning Model Connected obtained an effect size value eye lesson chemistry higher than physics, biology and Integrated IPA, and Influence Integrated Science Learning the Connected Model on learning outcomes has the highest effect when use type statistics Pretest - posttest one group only.